Potensi Antibakteri Sediaan Sabun Cair Ekstrak Kulit Nanas (Ananas comosus L. Merr.) Terhadap Bakteri Staphylococcus aureus ATCC 25923 - Ismi Rahmawati; Riesky Maulida; Siti Aisyah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Pineapple peels extract (Ananas comosus (L.) Merr.) has antibacterial activity against Staphylococcus aureus bacteria which causes skin infections. One of the infection prevention is by using antibacterial hand soap. This study aims to determine the physical quality, stability and antibacterial activity of the pineapple peels extract soap against S. aureus ATCC 25923. Pineapple peels extract obtained from maceration with 70% ethanol solvent was formulated into liquid hand washing soap. Soap formulations were made with the respective concentrations of 3%, 6%, and 9%. Each formula was tested for physical quality with parameters: organoleptic, homogeneity, pH, specific gravity, viscosity, and foaming capacity. Stability test using the freeze thaw method with organoleptic , pH, and viscosity. The formulation results were tested for antibacterial activity against S. aureus ATCC 25923 by the well diffusion method. Panelists testing was done with several respondents. Data analysis of physical quality, stability and activity was tested by SPSS statistics with a confidence level of 95%. Pineapple peel extract contains flavonoids, alkaloids, tannins, saponins and phenols. All three soap formulas have physical quality in accordance with SNI 2588: 2017. The three formulas are stable until the fifth cycle (one cycle of 48 hours). The three liquid soap formulas had antibacterial activity against S. aureus ATCC 25923. The formula with a concentration of 9% was not significantly different from the positive control and had the highest inhibitory diameter of 21.78 ± 0.84mm. The formula with a concentration of 9% were most preferred by the panelists.